Employee Recruitment Process Analysis of PT. Wishan Global Medika Tangerang Banten Indonesia - Indra Ora Emi, Yohanes; Erlina Puspitaloka Mahadewi; Susi Shorayasari; Rini Handayani (International Journal of Science, Technology & Management, 2022)
The present study reports the first comprehensive study around employee recruitment, inside the era of globalization has led to intense competition in various industrial fields, including the medical and healthcare industry. PT. Wishan Global Medika (WGM) is a medical evacuation company in Tangerang Banten Indonesia, to face competitors the company needs to carry out employee recruitment activities in accordance with the vision and mission in order to achieve the goals the company wants to achieve. Product from Indonesian medical companies are still quite considered in the global market but still has competitor from countries in Southeast Asia. One way to face this competition is that companies are required to have competent and good performance employees. The purpose of this study was to analyze the employee recruitment process at PT. Wishan Global Medika Tangerang Banten. The conceptual framework of the employee recruitment process in this study includes 3 items, namely Sourcing, Selection Process, and User Process. The research method used is qualitative research with in-depth interviews with a case study approach. Purposive sampling was used with a total of 3 respondents, namely the main director, general manager and human resources staff. The results of the study indicate that the analysis of human resource management in this company still does not lead to the interests of the company and determines the types of tasks and jobs that need to be carried out and there is no management policy rules in order to support the strategy of human resource management. The analysis of the employee recruitment system in the company is considered to be in accordance with the standart operating procedures recruitment, also still needs to be improved in terms of sources and stages of recruitment so as to minimize obstacles in recruitment. The conclusion of this study is that the implementation of human resource development needs to be carried out in an integrated manner in long-term and annual corporate planning as well as improving the quality of recruitment so as to prevent the occurrence of vacancies.